2012
DOI: 10.4021/jocmr865w
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Feed Forward and Feedback Signaling for Inflations and Chest Compression Pressure During Cardiopulmonary Resuscitation in a Newborn Mannequin

Abstract: BackgroundThe objective of the study was to evaluate a device that supports professionals during neonatal cardiopulmonary resuscitation (CPR). The device features a box that generates an audio-prompted rate guidance (feed forward) for inflations and compressions, and a transparent foil that is placed over the chest with marks for inter nipple line and sternum with LED’s incorporated in the foil indicating the exerted force (feedback).MethodsTen pairs (nurse/doctor) performed CPR on a newborn resuscitation mann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 17 publications
(15 reference statements)
0
6
0
Order By: Relevance
“…A commonly used duration of CPR cycles in this type of research is 90 seconds or 2 minutes [9,10]. We chose to perform each intervention in series of 10 × 2 minutes.…”
Section: Methodsmentioning
confidence: 99%
“…A commonly used duration of CPR cycles in this type of research is 90 seconds or 2 minutes [9,10]. We chose to perform each intervention in series of 10 × 2 minutes.…”
Section: Methodsmentioning
confidence: 99%
“…Sixteen studies compared CC feedback devices including 12 manikin studies,69–80 3 animal studies81–83 and 1 clinical study 84. Studies assessed auditory visual feedback devices,69 70 75 78 79 visual feedback alone,71 auditory feed forward devices,72–74 76 77 haptic feedback device80 and real-time physiological feedback using capnography81–83 or blood pressure84 monitoring.…”
Section: Resultsmentioning
confidence: 99%
“…Sixteen studies compared CC feedback devices including 12 manikin studies,69–80 3 animal studies81–83 and 1 clinical study 84. Studies assessed auditory visual feedback devices,69 70 75 78 79 visual feedback alone,71 auditory feed forward devices,72–74 76 77 haptic feedback device80 and real-time physiological feedback using capnography81–83 or blood pressure84 monitoring. Overall, studies reported a significant improved CC depth,70 79 CC rate,69 70 79 duty cycle69 70 79 and percentage of correctly performed cycles75 when using an auditory-visual feedback device (table 4).…”
Section: Resultsmentioning
confidence: 99%
“…CPR effectiveness depends on interplay between physiological, mechanical and pedagogical aspects. Real-time feedback systems for CC rate and depth in neonatal CPR are evolving53 54 and may potentially be useful in teaching and training, as well as clinical CPR. Such systems also allow for force-targeted and pressure-targeted rather than depth-targeted CC.…”
Section: Resultsmentioning
confidence: 99%